PENGEMBANGAN MODUL PRAKTIKUM MEKANISME ENGINE SEPEDA MOTOR 4 LANGKAH BERBASIS PROBLEM BASED LEARNING - Wilyanto Karim; Muhammad Yasser Arafat; Hasanuddin Hasanuddin; Monica Pratiwi; Esta Larosa; Sugeng Pramudibyo (Jambura Journal of Engineering Education, 2023)
ABSTRACT The study aims to develop a module of motor mechanics four-step motorcycle based problem based learning on the mechanical engineering education program of the gorontalo state college of engineering. Research in the development of the module lab uses RD (research and development) development methods. The research method referred to the 4-d model (four-d models). Based on research and analysis of already conducted validation data analysis it can be concluded that the validation of the module's practical-based problem learning on its engine engine trainer tool 4 steps from the engine engine aspect of media worthiness are defined as worthy by the validator atan 80% percentage, and of the appropriatical value of these service modules is gained a feasibility percentage of 91.50%.Keywords: development, module practical, the problem of based learning.